Escritura publicitaria en el tránsito entre el medievo y la modernidad - Alejandro García Morilla (Medievalista)
The international scientific community has no doubts today in assuming that the inscriptions are a means of communication with the intention of notoriety, universality -within the social group that gives rise to them- and a greater or lesser degree of durability. Hence, it has been the mechanism used, among others, by artists and sculptors to accompany their iconographic programs with the intention of completing them and offering greater communicative depth than that which can be achieved solely with images. This is undoubtedly the objective pursued by the artist (or artists) who created the altarpieces of Doubt and Passion for the Caparroso funeral chapel in Pamplona Cathedral. This mechanism – text+image –, does not represent any novelty, but the use of different graphic types within the same epigraphic group does. This phenomenon is characteristic of and almost exclusive to the epigraphy of the transition between the medieval decline and the dawn of modernity. That is why our study focuses on the paleographic analysis of these altarpieces trying to shed light on some unknowns that still remain unresolved.